Pelatihan Pembuatan Pelengkap Busana Untuk Souvenir dan Aksesoris Hantaran - Ariyana Damayanti (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2025)
Women's empowerment activities are currently very much needed as a form of increasing abilities and skills. Skills can be used as additional abilities that can have economic value so that they can improve the economy. As women, it is time to show their quality that women are also able to be creative in other fields. This training is provided in order to provide experience, knowledge and skills in the field of making accessories and souvenirs as a complement to the delivery to the training participants. Participants in this training are taught techniques for making accessories, making souvenirs, assembling accessories for deliveries and folding techniques in making souvenirs. A series of processes for making accessories and souvenirs are expected to be able to produce skills in the field of fashion that have good quality to attract customer interest. This training is expected to have many benefits that can be taken and applied by participants after completing a series of training activities and returning to their respective activities. The results of the training are expected to be able to be applied to the lives and business fields of participants to improve the economy. The training methods used are interactive methods, demonstration methods, and question and answer methods. This training produces creativity in making souvenirs and accessories that complement deliveries that have economic selling value.